HISTORY OF THE GOOD SPIRIT FLUTTERING ROUND THE LIBRARIES, BOOKS AND READING IN NORDIC AND BALTIC COUNTRIES - KRAULS, INETA (Knygotyra, 2014)
Lietuvos nacionalinė Martyno Mažvydo bibliotekaGedimino pr. 51, LT-01504 Vilnius, LietuvaEl. paštas ineta.krauls@gmail.com